Food consumption based on processing level (according to Nova system) during the COVID-19 pandemic among adolescents with immunocompromised conditions: a case-control study - Esteves, Gabriel P.; Mazzolani, Bruna Caruso; Smaira, Fabiana Infante; Santo André, Heloísa C.; Iraha, Amanda Yuri; Astley, Camilla; Marques, Isabela Gouveia; Amarante, Milla Cordeiro; Rezende, Nathalia Saffioti; Sieczkowska, Sofia Mendes; Franco, Tathiane Christine; do Amaral Miranda, Luana Cristina; et al. (Frontiers in Nutrition, 2023)
The COVID-19 pandemic impacts on eating habits among adolescents may be more relevant in pediatric patients with immunocompromised chronic diseases. This case-control study conducted between June and October 2020 aimed to: i) describe dietary patterns of adolescents with chronic conditions compared to healthy controls; and ii) determine associations between food consumption, health-related quality of life (HRQL) and sleep quality during the COVID-19 pandemic. Participants (184 immunocompromised and 58 healthy adolescents, aged 14.3 [SD 2.5]) responded to HRQL and sleep validated instruments (PedsQL and PSQI) and three 24-hour food recalls via online software. Adjusted linear and logistic regressions were used to assess differences in dietary patterns and associations between food consumption (according to Nova classification) and HRQL and sleep quality. Adolescents with gastrohepatic, rheumatic, and kidney diseases had a better dietary pattern vs. their healthy peers, showing greater consumption of unprocessed and minimally processed foods (unstandardized coefficient (b)=7.35 %[95%CI 1.59; 13.1]; b=15.10 %[95%CI 7.00; 23.1]; and b=11.2 %[95%CI 5.68; 16.8]), and lower consumption of ultraprocessed foods (b=7.53 %[95%CI -12.90; -2.18]; b=-11.4 %[95%CI -18.90; -3.94]; b=-10.8 %[95%CI -16.00; -5.68]). Consumption of culinary ingredients was associated with reduced psychological HRQL in controls (standardized coefficient (β)=-0.26[95%CI -0.52; -0.004]), and processed food consumption was associated with improved sleep latency in immunocompromised participants (β=0.16[95%CI 0.01; 0.31]). These findings suggest diet quality may play a role in HRQL and sleep quality in this population, and may be relevant for clinical practitioners and policy makers when considering the importance of dietary quality in immunocompromised youths.